Influence of inflammatory plasma biomarkers on choroidal thickness in type 2 diabetes mellitus. Issue 1 (January 2023) - Bartol-Puyal, Francisco de Asís; Isanta, Carlos; Verdes, Guayente; Ruiz-Moreno, Óscar; Calvo, Pilar; Pablo, Luis
Purpose: To assess the influence of inflammatory plasma biomarkers on choroidal thickness (CT) in patients with type 2 diabetes (T2D). Methods: Cross-sectional study enrolling T2D patients and age-matched healthy controls (>55 years of age, Caucasian, axial length <26 mm, no macular edema, and naïve). Patients were examined with swept-source OCT Triton, obtaining automatic measurements. CT was analyzed using the ETDRS grid and the recently proposed choroidal division. A blood analysis was commanded: general biochemical profile, liver status, T2D status, thyroid and parathyroid activity, coagulation, general immunological profile, and inflammatory biomarkers. Results: 124 eyes of 124 patients with a mean age between 66 and 68 years were examined. The new choroidal division showed differences between groups (p < 0.05) in more sectors than the ETDRS grid, and more biomarkers influenced these new sectors. T2D patients had higher levels of IL-8, TNF-α, MCP1, adiponectin and L-selectin. CT was influenced by TNF-α, IL-17, leukocytes and erythrocyte sedimentation rate, as well as by HDL cholesterol, albumin, liver function biomarkers, and TSH. HbA1c showed little influence on CT. Conclusions: T2D patients present increased plasma inflammatory biomarkers, exhibiting an influence on CT. IL-17 is related to a thicker choroid but TNF-α is related to a thinner choroid. HbA1c has little influence on CT. The recently proposed choroidal division is more sensitive to CT changes than the ETDRS grid. Some sectors are more sensitive to plasma biomarkers.